2004
DOI: 10.1080/00365590410018675
|View full text |Cite
|
Sign up to set email alerts
|

Voiding Position does not Affect Uroflowmetric Parameters and Post‐void Residual Urine Volume in Healthy Volunteers

Abstract: Urinary flow rates and PVR urine volume do not seem to be affected by voiding position in healthy men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 7 publications
4
73
0
4
Order By: Relevance
“…They authors reported that these different positions do not have an effect on uroflowmetric parameters and PVR. 7 The authors also compared the uroflowmetric parameters and the PVR volume in healthy women in sitting and crouching positions; similarly, they could not find a significant difference between the positions. 7 Riehmann and colleagues reported that standing is better than the recumbent position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They authors reported that these different positions do not have an effect on uroflowmetric parameters and PVR. 7 The authors also compared the uroflowmetric parameters and the PVR volume in healthy women in sitting and crouching positions; similarly, they could not find a significant difference between the positions. 7 Riehmann and colleagues reported that standing is better than the recumbent position.…”
Section: Discussionmentioning
confidence: 99%
“…The best position for emptying the bladder is controversial and not yet established. [7][8][9][10][11][12][13][14][15][16][17][18][19] There are no studies which assess the effects of alpha blockers on PVR volumes in different voiding positions. We evaluated the effect of the sitting and standing voiding positions on uroflowmetric parameters and PVR in patients over 50 years old and with LUTS due to BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Uroflowmetric measurements could be done in a sitting or crouching position in women. It has been demonstrated that there is no difference between these positions regarding the uroflowmetric parameters (9). Nevertheless, we instructed the subjects to void in a sitting position to provide standardization.…”
Section: Discussionmentioning
confidence: 99%
“…Hemen sonrasında üroflovmetri işlemi (MMS, Hollanda) cihazı ile yapıldı ve takiben suprapubik yöntem ile postmiksiyonel rezidüel idrar (PVR) ölçümleri yapıldı. Hastalar IPSS'lerine göre 3 gruba ayrıldı, skoru hafif olan hastalar grup 1 (IPSS; 0-7), orta olanlar grup 2 (IPSS: [8][9][10][11][12][13][14][15][16][17][18][19] Prostat volümü tahmin etmede parmakla rektal muayene, abdominal ve transrektal ultrason, manyetik rezonans görüntüleme sıklıkla kullanılan yöntemlerdir. BPH klinik semptomlarının PV ile ilişkili olmadığı bilinen bir durumdur.…”
Section: Yöntemlerunclassified
“…Üroflovmetri ve PVR ile birlikte infravezikal obstrüksiyonu olan hastaların değerlendirilmesinde kullanılan basit, noninvaziv, güvenilir bir tetkikdir. Ancak, çalışmanın çekin-cesini oluşturmak açısından üroflovmetri ölçümleri, yaş, cinsiyet, işenen idrar volümü, hastanın psikolojik durumu, üreter kateterizasyonu ve işeme pozisyonu gibi çeşitli faktörler tarafından etkilenebilir (16,19). Bizim çalışmada IPSS ile üroflovmetri maksimum akış arasında orta-iyi derecede negatif bir bağıntı varken, üroflov-metri ortalama akış ile arasında daha iyi negatif bir ilişki olduğu-nu bulduk, yapılan çalışmalarda maksimum akışın daha değerli olduğu ve obstruksiyonu tahmin etmede daha iyi bir parametre olduğu bildirilmiştir (20,21).…”
Section: Yöntemlerunclassified